Self-concept Profiles in Vocational High School Students Level - Ani Kurniati; Juliejantiningsih, Jovita; Wahyuni, Sri (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The purpose of this study was to determine the description of the self-concept of second-grade students at SMK N 6 Semarang. The research method used is descriptive quantitative with survey research type. The number of samples was 70 students. Sampling using a random sampling technique. The results of the research on the description of the self-concept that has a high self-concept amounted to 10 students with a percentage of 14%. Students who have a moderate self-concept amounted to 49 with a percentage of 70% and students who have a low self-concept or negative self-concept amounted to 11 with a percentage of 16%. The results of this study are presented for guidance and counseling teachers in schools to be used as a basis for efforts to provide guidance and counseling services to students to increase positive self-concept at SMK N 6 Semarang.